PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA MATERI NILAI-NILAI PANCASILA MENGGUNAKAN MEDIA POP UP BOOK KELAS IV - AZIZAH AZZAHRA; Nahrun Amirus Shodiq; Rizka Marliana; Wahyu Widiyatmoko (LPPM Universitas Cipta Mandiri, 2025)
This study was motivated by the low learning outcomes of fourth grade students in Pancasila Education subjects, especially on the material of practicing the values of Pancasila, One of the causes is the lack of use of interesting and contextual learning media so that students have difficulty in understanding abstract material This study aims to improve student learning outcomes through the use of pop up book media that is visual, interactive, and fun. This type of research is Classroom Action Research (PTK) which was carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The subjects of this study were students of class IV B SD Muhammadiyah 4 Surakarta, totaling 20 students. Data collection techniques used observation, learning outcome tests, and documentation. The results showed that the use of pop up book media can significantly improve student learning outcomes In cycle I, the completeness of student learning outcomes reached 65%, and increased to 85% in cycle II. In addition to improving learning outcomes, the use of this media also encourages active involvement of students in the learning process Pop up book media is able to present Pancasila values material concretely and interestingly. Thus, pop up book media is proven effective in improving learning outcomes and student activeness on the material of practicing Pancasila values. This media is recommended to be used in learning Pancasila Education in elementary schools.